Prevalência dos principais enteropatógenos em bezerros da fase de aleitamento em explorações leiteiras semi-intensivas de duas bacias leiteiras do estado de Minas Gerais - Marina Guimaraes Ferreira (2009)
The objective of this study was to establish the prevalence of intestinal pathogens that cause diarrhea in suckling female calves in twenty dairy farms of semi-intensive systems, in the central west and Alto Paranaíba region of Minas Gerais state in Brazil. It was collected 319 feces samples to proceed EPG and OOPG exams, with identification of species of Eimeria by the sporulation of samples in potassium dichromate 2,5%. Questionnaires were used to identify characteristics of management and environment of the farms studied. One hundred thirty tree samples were maintained in -200C and submitted to analysis for identification of Salmonella spp and Escherichia coli using the culture media and biochemistry tests. It was used ELISA commercial kit to identify virus (Rotavirus and Coronavirus), bacteria (Escherichia coli F5) and protozoa (Cryptosporidium parvum) in 87 samples of animals until 60 days age. The prevalence of Eimeria was 48,23%, helminths (15,36%), Escherichia coli (90,22%), Rotavirus (8,0%), Cryptosporidium parvum (9,2%) and it was not identified positive samples for Salmonella spp, Coronavirus and Escherichia coli F5. The species of Eimeria zuernii and Eimeria bovis were the most frequent among the species of Eimeria